Biometrical Studies on the Tassar Silk Cocoon (Antheraea paphia L.) of Orissa - Panda, N. (Indian Forester, 1972)
Tassar seed cocoons were collected from important regions of Orissa towards the latter part of August. Cocoons were separated according to their peduncle characters, colour and sex. Important cocoon characters were determined quantitatively in different groups and analysed statistically. Correlation coefficient values for different characters were calculated. It was observed that female cocoons were significantly heavier than males irrespective of variety and colour, but shell weight was positively associatcd with colour of cocoons and also sex. The Black and Yellow-coloured cocoons had the highest shell weight and Cream the lowest. ’Nadia’ variety had longer peduncle than ’Bogai’; colour of cocoons had significant bearing on peduncle length irrespective of variety. Cream-coloured cocoons had the longest peduncle with narrow loop and Yellow the shortest with widest loop. Thus higher shell weight was founa in Yellow or Black-coloured cocoons with shorter peduncle and wider loop.